How to place the duality of specific MMP-9 inhibition for treatment of inflammatory bowel diseases into clinical opportunities? - Opdenakker, Ghislain; Vermeire, Séverine; Abu El-Asrar, Ahmed (Frontiers in Immunology, 2022)
Crohn’s disease (CD) and ulcerative colitis (UC) are inflammatory bowel diseases (IBD) with the involvement of immune cells and molecules, including cytokines, chemokines and proteases. A previous extensive review about the molecular biology of matrix metalloproteases (MMPs) and tissue inhibitors of metalloproteases (TIMPs), related to intestinal barrier destruction and restoration functions in IBD, is here complemented with the literature from the last five years. We also compare IBD as a prototypic mucosal inflammation of an epithelial barrier against microorganisms with inflammatory retinopathy as a disease with a barrier dysfunction at the level of blood vessels. Multiple reasons are at the basis of halting clinical trials with monoclonal antibodies against MMP‐9 for IBD treatment. These include (i) the absence of a causative role of MMP‐9 in the pathology in animal models of IBD, (ii) the fact that endotoxins, crossing the intestinal barrier, induce massive local release of both neutrophil collagenase (MMP‐8) and gelatinase B (MMP‐9), (iii) insufficient recognition that MMPs modify the activities of cytokines, chemokines and their receptors, and (iv) the fact that MMPs and TIMPs act in an interactive network, possibly having also beneficial effects on IBD evolution. Nevertheless, inhibition of MMPs may be a useful therapeutic approach during specific IBD disease phases or in specific subphenotypes. This temporary “window of opportunity” for MMP‐9 inhibition may be complemented by a locoregional one, provided that the pharmacological agents are targeted in time to affected tissues, as is achieved in ophthalmological inflammation. Thus, in order to discover spatial and temporal windows of opportunity for MMP inhibition as treatment of IBD, more preclinical work including well controlled animal studies will be further needed. In this respect, MMP‐9/NGAL complex analysis in various body compartments is needed for better stratification of IBD patients who may benefit from anti‐MMP‐9.